Analysis of the Role of the Regional III Airport Authority Office in Supervising Terminal 1 Facilities at Juanda International Airport, Surabaya - Tasyania, Sellina Iko; Istiyani, Yuniar (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Region III Airport Authority Office is a government agency that has the authority to carry out supervision to ensure safety and smooth flights in accordance with Minister of Transportation Regulation Number 41 of 2011. The Airport Authority Office carries out supervision in the field of airport facilities and equipment, airport services and operations . The aim of this research is to determine the role and inhibiting factors of the Regional III Airport Authority Office in monitoring terminal 1 facilities at Juanda International Airport, Surabaya. The research method used is qualitative. Qualitative research is a research process by understanding the phenomena that occur, writing down the data obtained from informant sources, then presenting it in the form of word descriptions. Data sources were obtained from primary data and secondary data, with data collection techniques using observation, interviews and documentation at the Regional III Airport Authority Office. The results of this research indicate that the role of the Regional III Airport Authority Office is to carry out inspections at terminal 1 facilities, airport operator PT Angkasa Pura 1, as well as Level of Service (LoS) inspections during Nataru and Angleb at Juanda International Airport. The inhibiting factors are human resources who are less competent in the field of facility supervision, unclear inspection schedule information, and the insufficient availability of operational vehicles.